2022
DOI: 10.1111/pedi.13438
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement efforts in a safety net institution: Increased diabetes screening is associated with lower HbA1c at diagnosis and improved HbA1c outcomes in youth with type 2 diabetes

Abstract: Objectives Evaluate whether increased diabetes screening in youth is associated with lower HbA1c at T2D diagnosis and improved HbA1c outcomes in youth. Research design and methods Diabetes screening rates from 2009 to 2018 were calculated. Electronic medical records identified obese youth ages 8–18 with first HbA1c ≥6.5% from 2009 to 2018; chart review confirmed incident T2D. Demographics, BMI and HbA1c values, and use of glucometer and diabetes medications were collected. Results 142 youth had T2D. Median age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Many clinical studies and trials suggested that HbA1c levels may be associated with cardiovascular disease [ 10 ], diabetic stroke, diabetic nephropathy, chronic microvascular complications and fundus oculi lesion, etc. So far HbA1c has been recommended for screening and diagnosis of diabetes by American Diabetes Association [ [11] , [12] , [13] ]. Similar recommendations were proposed by WHO as well as other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical studies and trials suggested that HbA1c levels may be associated with cardiovascular disease [ 10 ], diabetic stroke, diabetic nephropathy, chronic microvascular complications and fundus oculi lesion, etc. So far HbA1c has been recommended for screening and diagnosis of diabetes by American Diabetes Association [ [11] , [12] , [13] ]. Similar recommendations were proposed by WHO as well as other countries.…”
Section: Introductionmentioning
confidence: 99%